Monascin abrogates RANKL-mediated osteoclastogenesis in RAW264.7 cells via regulating MAPKs signaling pathways - Cheng, Yin; Liu, Haixia; Li, Jing; Ma, Yujie; Song, Changheng; Wang, Yuhan; Li, Pei; Chen, Yanjing; Zhang, Zhiguo (Frontiers in Pharmacology, 2022)
Osteoclasts (OCs) are multinucleated cells that play a major role in osteolytic diseases such as osteoporosis. Monascin (Ms) is one of the active substances in the traditional Chinese medicine red yeast rice. Studies have found that red yeast rice can maintain bone health. In this study, the anti-osteoclastogenesis effects of Ms on RANKL-induced RAW264.7 cells were assessed, and the underlying mechanism was investigated. Ms exhibited inhibitory effects on OC differentiation and formation in a dose-dependent manner and suppressed the bone-resorbing activity of mature OCs. Ms blocked OCs-typical genes (c-Fos, NFATc1, CSTK, MMP-9, TRAP, ITG-β3, OSCAR and DC-STAMP). Furthermore, Ms treatment considerably inhibited the activation of MAPKs, JNK and p38. Taken together, Ms suppresses RANKL‐induced osteoclastogenesis of RAW264.7 cells by restraining MAPKs signaling pathways and is a potential therapeutic option as a novel OC inhibitor to mitigate bone erosion.